Childhood Obesity, Unrecognized Public Health Challenge in Nepal - Aryal, M (Kathmandu University Medical Journal, 2012)
No abstract available. DOI: http://dx.doi.org/10.3126/kumj.v8i4.6229 Kathmandu Univ Med J 2010;8(4):358-9